Change in scalding fluids by time in poultry slaughterhouse and its effect on microbiological quality of carcasses - Incili, Gokhan Kursad; Calicioglu, Mehmet (Wiley, 2018)
The objective of this study was to investigate the effect of the condition of scalding on the microbiological quality of the chilled carcasses. For this purpose, clean (A) or dirty (B) water was used for scalding, samples were collected in every 30 min for 150 min from each of three scalding tanks (Tank 1, Tank 2, Tank 3), from drips collected after defeathering and inner-outer bird washing steps, and from chilled carcasses (C). All samples were analyzed for the microbiologically and also physicochemical parameters of scalding fluids. Total aerobic counts significantly increased in all of the scalding tanks as the time progress in both groups A and B. As a result, effect of scalding with clean water on microbiological quality of the broiler carcasses disappeared within the first 30 min, and no meaningful difference was found during the remaining time period. Practical applicationsScalding is carried out at static water using either clean or dirty water in small or medium-size broiler slaughterhouses. Organic substances, dry matters, and protein levels in scalding tanks increase by the time and these parameters effects the carcass contamination. In this study, moderate correlation was found between the organic matter level in the scalding tanks and the numbers of coliform bacteria of the carcasses. This correlation between the level of organic matter in the scalding water and coliform bacteria may indicate that this parameter can have a potential to be used as critical limit in plants using clean water-scalding.
Keywords: Broiler Carcasses; Listeria-Monocytogenes; Chicken Carcasses; Contamination; Water; Meat; Decontamination; Establishment; Points; Turkey